Review: Perbandingan Compounding Konvensional dan Modern dalam Pembuatan Sediaan Farmasi Berbahan Kunyit (Curcuma domesticaVal.) - Dewi, Kadek Ratna Sari; Dewi, Gusti Ayu Surya Ciptha; Dewi, Gusti Ayu Putu Putri Kirana; Pangesti, Ni Made Dinda Pradnya; Rahmasari, Luh Putu Citramas Pradnya; Yuda, I Gusti Ayu Sinta Amara; Yayanasri, Yayanasri; Devi, Putu Ayu Sri; Pramiari, I Gusti Agung Istri Agung; Saputra, Kadek Angga Dwi; Mahindra T., I Kadek Sindhu Satya; Pradnyana, I Gede Krishna Wira; et al. (Jurnal Farmasi Udayana; Vol. 13, No. 2, Tahun 2024, 2025)
Conventional compounding practices in traditional medicine have been established for many years; however, they often encounter challenges in ensuring product quality, consistency, and safety. This study aims to compare conventional and modern compounding methods in the preparation of pharmaceutical products derived from turmeric rhizomes ( Curcuma domestica Val). The research employs a literature review, drawing from a selection of studies related to the formulation of these pharmaceutical products from accredited scientific databases. The obtained data were analyzed descriptively to evaluate the comparison between the two methods in terms of effectiveness, stability, safety, and cost. The findings reveal that both methods possess distinct advantages and disadvantages, offering valuable insights into key aspects of producing pharmaceutical preparations from turmeric rhizomes. Ultimately, this research enhances the understanding of each method's implications in pharmaceutical production, particularly within the realm of traditional medicine.